COMPLETENESS OF THE LIST OF SPINOR REGULAR TERNARY QUADRATIC FORMS. Issue 2 (5th December 2018) - Earnest, A. G.; Haensch, Anna
Abstract : Extending the notion of regularity introduced by Dickson in 1939, a positive definite ternary integral quadratic form is said to be spinor regular if it represents all the positive integers represented by its spinor genus (that is, all positive integers represented by any form in its spinor genus). Jagy conducted an extensive computer search for primitive ternary quadratic forms that are spinor regular, but not regular, resulting in a list of 29 such forms. In this paper, we will prove that there are no additional forms with this property.